Adoptarunt et levarunt: Godparents of Illegitimate Children in the 18th Century Vilnius Deanery - Jonaitytė, Ugnė (Lietuvos istorijos studijos, 2024)
This article explores a previously uninvestigated topic: the role of godparents for illegitimate children in the 18th century Vilnius deanery. The research is based on analysing baptism records from parishes within the Vilnius deanery during this period. The study delves into the selection of godparents for illegitimate children, investigating such factors as the number of godparents present at the baptism and whether they acted as spiritual guardians for multiple illegitimate children. Additionally, it examines the social status of the godparents, analyzing surnames, social standing, and place of residence to determine possible kinship, social, and territorial relations with the parents. Furthemore, the paper explores whether relationships between godparents and illegitimate children extended beyond the formal baptism ceremony.